2020
DOI: 10.1007/s42770-019-00222-y
|View full text |Cite
|
Sign up to set email alerts
|

High-performance method to detection of Klebsiella pneumoniae Carbapenemase in Enterobacterales by LC-MS/MS

Abstract: Carbapenem-resistant Enterobacterales (CREs) have been recognized as an important threat to global health. CRE cause the majority of the difficult-to-treat infections in health-care settings and are associated with high mortality. Klebsiella pneumoniae carbapenemase (KPC)-producing CREs, in particular Klebsiella pneumoniae, are globally disseminated and responsible for a large number of outbreaks. Development of rapid methods for KPC detection can provide great clinical and epidemiological benefits to prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Controversially, Sidjabat et al observed changes in the proteome in the presence of drug only, with the drug-negative proteome reflecting that of the susceptible control [52] . However, studies employing targeted methods suggest that resistant and susceptible phenotypes differ even in the absence of drug stress [53] , [54] , [55] , [56] .…”
Section: Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Controversially, Sidjabat et al observed changes in the proteome in the presence of drug only, with the drug-negative proteome reflecting that of the susceptible control [52] . However, studies employing targeted methods suggest that resistant and susceptible phenotypes differ even in the absence of drug stress [53] , [54] , [55] , [56] .…”
Section: Proteomicsmentioning
confidence: 99%
“…The diagnostic performance of the peptides resulted in an overall accuracy of 100 % with a turnaround time <90 min. Lovison et al later adapted and validated the method and reported a sensitivity of 96.07 % and specificity of 100 % [56] . Similar protocols have been published for the detection of NDM and OXA-48-like CP isolates [53] , [55] .…”
Section: Proteomicsmentioning
confidence: 99%